Prevalence of HPV in Oral Squamous Cell Carcinoma Patients - Dr. Vinod Ramesh Mahajan; Dr. Shridhar Pandurang Patil; Dr. Atul Ramdas Sonar; Dr. Dhananjay Shridhar Borole; Dr. Reshma Wankhede (Nirmale), (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Human Papillomavirus (HPV) has been established as a contributing factor in various cancers, with increasing evidence linking it to Oral Squamous Cell Carcinoma (OSCC). This study aims to determine the prevalence of HPV in OSCC patients and identify the most frequent HPV types associated with the disease. Methods: A cross-sectional study was conducted on 200 patients diagnosed with OSCC at a tertiary care center. Samples were collected and tested for HPV DNA using Polymerase Chain Reaction (PCR) targeting high-risk HPV types. Demographic and clinical data were also analyzed to assess correlations between HPV status and clinical characteristics such as age, sex, and tumor stage. Results: Out of the 200 patients, 32% tested positive for HPV. HPV-16 was the most prevalent type, found in 24% of the patients, followed by HPV-18, HPV-31, and other types at lower frequencies. Statistical analysis revealed significant associations between HPV positivity and younger age (<40 years), male sex, and advanced tumor stages (III-IV). Conclusion: The study confirms a significant presence of HPV in patients with OSCC, predominantly HPV-16. The high prevalence in younger patients and those with advanced disease stages suggests that HPV is an important factor in the etiology and progression of OSCC. These findings highlight the need for further research into HPV as a marker for early detection and a potential target for vaccination and therapeutic strategies in OSCC.